BENTUK DAN FUNGSI AKSARA BALI PADA UPACARA DEWA YADNYA DI BALI - Yuni Swari, Ni Putu Ayu (Humanis; Volume 13. No.3. Desember 2015, 2016)
Balinese script is one of the cultural heritage that has been handed down from generation to generation therefore it is very important for the research. This research, aims to understand the form and function of the Balinese in dewa yadnya ceremony.  In addition, this research   intend to  inventory of the Balinese culture, especially in the form of holy script in Bali. The basic theory in this research is the theory of phonology and culture linguistic theory. Methods and techniques in this study is divide into three stages, which are methods and techniques of providing data are using conversation  and listen method, accompani by record and photograph technique; methods and data analysis techniques using qualitative methods with which combined with the techniques of descriptive analitis; and methods and techniques of presenting the results of the data analysis are using  formal and informal methods, with inductive and deductive techniqu. The results obtain in this research is a script that is used in ceremonies of dewa yadnya are holy script bijaksara/wijaksara and modre script. The forms of the sacred letters, contain in Nasarin ceremony, Mendem pedagingan, Mlaspas, and Ngenteg Linggih. The functions contain in dewa yadnya ceremony are metalingual functions. Metalinguial  function is translated into 5 functions, which are : ( 1 ) as a cultural identity; ( 2 ) as a symbol of divinity; ( 3 ) as a magical symbol; ( 4 ) as a symbol of purification; ( 5 ) as a symbol of strength.
Keywords: form, function, ceremony